Development of technology of nitride films manufacture for blades of gas turbine engines - Ігнатович, С.Р.; Орланов, В.Й.; Чумак, О.І. (Proceedings of National Aviation University (archive), 2004)
Films of TiN on compressor blades of gas turbine engines are considered. Films are obtained with using plasma jet coater of capillary pulse-periodical plasmatrone. Diagnostics of films surface are performed.